Effect of Ca-P compound formed by hydrothermal treatment on biodegradation and biocompatibility of Mg-3Al-1Zn-1.5Ca alloy; in vitro and in vivo evaluation - Kim, Yu-Kyoung (Sci Rep, 2017)
Chemical combinations of Ca-P produced via plasma electrolytic oxidation (PEO) and a hydrothermal treatment were fabricated to improve the initial corrosion resistance and biocompatibility of a biodegradable Mg-3Al-1Zn-1.5Ca alloy. For the formation of an amorphous calcium phosphate composite layer on the surface of a magnesium alloy, a PEO layer composed of MgO and Mg(3)(PO(4))(2) was formed by PEO in electrolytes containing preliminary phosphate ions. During the second stage, a thick and dense Ca layer was formed by Ca electrodeposition after PEO. Finally, a hydrothermal treatment was carried out for chemical incorporation of P ions in the PEO layer and Ca ions in the electrodeposition layer. The amorphous calcium phosphate composite layer formed by the hydrothermal treatment enhanced osteoblast activity and reduced H(2)O(2) production, which is a known stress indicator for cells. As a result of co-culturing osteoblast cells and RAW 264.7 cells, the formation of amorphous calcium phosphate increased osteoblast cell differentiation and decreased osteoclast cell differentiation. Implanting the alloy, which had an amorphous calcium phosphate composite layer that had been added through hydrothermal treatment, in the tibia of rats led to a reduction in initial biodegradation and promoted new bone formation.